Green Credit Policy and Firms' Green Total Factor Productivity: The Mediating Role of Financial Constraints - JING, Fan; MUHAMAD, Haslinah; SAID, Ridzwana Mohd; DAUD, Zaidi Mat (Theoretical and Practical Research in Economic Fields, 2024)
In recent years, environmental pollution has emerged as a critical global challenge, prompting increasing attention toward the Green Credit Policy as a tool for environmental regulation. These policies aim to align financial systems with sustainability objectives, yet their impact on corporate development remains controversial. This study adopts the Propensity Score Matching-Difference-in-Differences (PSM-DID) method to analyze the effects of the Green Credit Policy on the green total factor productivity (GTFP) of Chinese listed companies over the period 2007–2022. The results reveal that while the Green Credit Policy is designed to enhance environmental performance, they have exacerbated financing constraints for enterprises, leading to a significant decline in GTFP. This negative impact is particularly pronounced in large enterprises and firms in eastern China, regions often subject to stricter environmental regulations. In contrast, the ownership type - whether state-owned or non-state-owned - does not significantly influence the outcomes, suggesting the pervasiveness of financing constraints across firms. The findings underscore the critical need for policymakers to design targeted green credit strategies that account for regional and enterprise-specific characteristics. For example, tailoring green finance mechanisms to address the challenges larger enterprises or firms face in economically developed regions could mitigate unintended consequences. Moreover, the study highlights the importance of integrating financial support mechanisms, such as tax incentives, subsidies, or green innovation funds, into the future Green Credit Policy. Such measures can promote investment in green technologies by alleviating financial pressures and fostering environmental and economic goals. Ultimately, this study advocates for a balanced, context-sensitive approach to green finance, ensuring sustainable development without compromising firms' productivity.